Formation of Si/organic interfaces using alkyne-functionalized cyclooctynes—precursor-mediated adsorption of linear alkynes versus direct adsorption of cyclooctyne on Si(0 0 1). (7th December 2018) - Länger, C; Heep, J; Nikodemiak, P; Bohamud, T; Kirsten, P; Höfer, U; Koert, U; Dürr, M
Abstract: Adsorption of ethynyl-cyclopropyl-cyclooctyne (ECCO), an alkyne-functionalized cyclooctyne, on Si(0 0 1) was studied by means of x-ray photoelectron spectroscopy (XPS) and scanning tunneling microscopy (STM). Together, XPS and STM results clearly indicate chemoselective adsorption of ECCO on Si(0 0 1) via a [2+2] cycloaddition of the strained triple bond of cyclooctyne without reaction of the ethynyl group. The results are compared to the adsorption of acetylene on Si(0 0 1): C2 H2 adsorbs on Si(0 0 1) via a precursor-mediated reaction channel as it was shown by means of temperature dependent measurements of the sticking probability as well as by means of STM experiments at variable temperature. On the other hand, cyclooctyne adsorbs on Si(0 0 1) via a direct reaction channel. This qualitative difference in the reaction pathways of the two functionalities leads to the observed chemoselective adsorption of ECCO via the strained triple bond of cyclooctyne. As the ethynyl group stays intact, monolayers of ECCO on Si(0 0 1) form a well defined interface between the silicon substrate and further organic molecular layers which can be attached to the ethynyl functionality.